Humanização no atendimento bancário - Vieira, Maria Eduarda (2022)
For many people, going to the bank branch has always been a nightmare, because going to the bank branch has always been synonymous with delay and stress. However, with the growth of digital banks, institutions face the challenge of promoting a better customer experience in order to keep you loyal and faithful. In this context, this article aims to better understand the need to implement more humanized care strategies in banking administrative processes, from the comparison between face-to-face and online processes. To achieve the goal, the mysterious client technique was used to make a comparison between the customer experience in the physical agency and in the digital bank, with the default as a situation to be solved. Reaching the end of the research, as the main result it is observed that the humanization of processes is attractive and can facilitate the conduction of a service in search of the expected results.